2019
DOI: 10.1186/s12877-019-1239-3
|View full text |Cite
|
Sign up to set email alerts
|

Health outcome of older hospitalized patients in internal medicine environments evaluated by Identification of Seniors at Risk (ISAR) screening and geriatric assessment

Abstract: Background Hospitals are in need of valid and economic screening and assessment tools that help identifying older patients at risk for complications which require intensified support during their hospital stay. Methods Five hundred forty-seven internal medicine in-patients (mean age 78.14 ± 5.96 years; 54.7% males) prospectively received Identification of Seniors at Risk (ISAR) screening. If screening results were positive (ISAR score ≥ 2), a comprehensive geriatric ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…For this reason, different methods have been suggested in the literature to admit older patients to emergency services. [21][22][23][24][25] In recent times, hospitals have begun to restructure their physical environments for older patients, and some have set up geriatric monitoring departments with bed capacities of four to seven. [20]…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, different methods have been suggested in the literature to admit older patients to emergency services. [21][22][23][24][25] In recent times, hospitals have begun to restructure their physical environments for older patients, and some have set up geriatric monitoring departments with bed capacities of four to seven. [20]…”
Section: Discussionmentioning
confidence: 99%
“…The available data were obtained prospectively. More detailed information about study cohort characteristics and methodology have previously been reported (see [13]). The study was approved by the ethics committee of the University Duisburg-Essen and need for consent was waived.…”
Section: Study Cohortmentioning
confidence: 99%
“…For high-risk patients with positive ISAR screening a comprehensive geriatric assessment (CGA) is recommended as a second diagnostic step. The ISAR screening in combination with the CGA has recently been validated for acute medical departments by Scharf et al [13]. Since the CGA is a timeand resource consuming assessment it is not efficient to perform CGA in all patients [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For high-risk patients with positive ISAR screening a comprehensive geriatric assessment (CGA) is recommended as a second diagnostic step. The ISAR screening in combination with the CGA has recently been validated for acute medical departments by Scharf et al [13]. Since the CGA is a time-and resource consuming assessment it is not efficient to perform CGA in all patients [14,15].…”
Section: Introductionmentioning
confidence: 99%